Overlap syndrome of autoimmune hepatitis and primary biliary cholangitis associated with portal vein thrombosis post COVID-19 - Zumaeta Rodríguez, Thalía Isabel (2021)
We present the case of a 53-year-old woman with a history of rheumatoid arthritis who, after recovering from a severe COVID-19, developed gastrointestinal bleeding as a manifestation of portal hypertension and progressive liver failure. Based on serology and ultrasound, an overlap syndrome of autoimmune hepatitis and primary biliary cholangitis associated with portal vein thrombosis were diagnosed. The response to steroids and anticoagulation was favorable. Hepatic involvement, induced by the virus, has been described in COVID-19. However, autoimmune diseases and thromboembolic phenomena can develop, having the liver as a target organ.